2011
DOI: 10.14713/pcsp.v7i2.1094
|View full text |Cite
|
Sign up to set email alerts
|

Extending Systematic Case Study Method: Generating and Testing Hypotheses About Therapeutic Factors Through Comparisons of Successful and Unsuccessful Cases

Abstract: This commentary focuses on two case comparison studies, one by Burckell and McMain (2011) on Dialectical Behavior Therapy for borderline personality disorder, and one by Watson et al. (2011) and Goldman et al. (2011) on Emotion-Focused Therapy for depression. The associated case comparison method, which evaluates and contrasts one successful case against one unsuccessful case that are both conducted in similar conditions, provides a unique opportunity for deepening our understanding of therapeutic change. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…For example, the above studies complement the quantitatively-based study of van Rijn et al (2011) which also found TA to be an effective therapeutic approach. Furthermore, as case study research accumulates, it becomes easier to make comparisons between cases and to increase specificity and transferability of findings by using cross-case analysis methods (Iwakabe and Gazzola, 2009;Iwakabe, 2011). This article concludes with a brief cross-case analysis which compares the findings from this case to others in this series.…”
Section: Introductionmentioning
confidence: 95%
“…For example, the above studies complement the quantitatively-based study of van Rijn et al (2011) which also found TA to be an effective therapeutic approach. Furthermore, as case study research accumulates, it becomes easier to make comparisons between cases and to increase specificity and transferability of findings by using cross-case analysis methods (Iwakabe and Gazzola, 2009;Iwakabe, 2011). This article concludes with a brief cross-case analysis which compares the findings from this case to others in this series.…”
Section: Introductionmentioning
confidence: 95%
“…The field of case study research in counseling and psychotherapy is now at a stage where a reasonably large number of rigorous case studies are available. A central priority, therefore, is to develop a credible strategy for acquiring knowledge from multiple cases, such as the "meta-synthesis" method (Iwakabe, 2009) mentioned above and discussed below.…”
Section: Meta-synthesismentioning
confidence: 99%
“…There have been many significant developments in the field of case study methodology in recent years, in relation to the use of adjudicational procedures, strategies for using case data to build theory, elaborating ethical frameworks, case comparison designs, and systematic cross-case analysis (i.e., "meta-synthesis" as a qualitative parallel to the meta-analysis method used in quantitative studies) (Iwakabe, 2009;McLeod, 2010). However, compared to the total annual output of counseling and psychotherapy research articles, it is still the situation that relatively few case studies are being published.…”
mentioning
confidence: 99%
“…Iwakabe (2011) asserts that case studies are an invaluable method of research as data is drawn from the fundamental unit in psychotherapy-direct contact between the therapist and client. He cites that this is advantageous as case studies provide information that manuals or group-based outcome research cannotnamely, concrete detail about how the therapy unfolds for a specific client and, through providing background information regarding the patient and therapist, useful contextual information regarding how a particular treatment was implemented.…”
Section: Pretest-posttest Vs "One-shot" Case Studymentioning
confidence: 99%